Systematic computer analysis of iron fumarate pharmacology in the treatment of iron deficiency and iron deficiency anemia - O. A. Gromova; I. Yu. Torshin; N. K. Tetruashvili (Акушерство, гинекология и репродукция)
Introduction. The use of the safest and most effective methods for iron deficiency (ID) compensation is implicated in current therapy of iron deficiency anemia (IDA). Oral administration of iron salts with organic acid anions is an important field in IDA therapy and prevention. Iron fumarate, being a divalent iron salt and the fumaric acid anion (a tricarboxylic acid cycle metabolite), is absorbed in vivo via gene-encoded molecular mechanisms specialized to interact primarily with fumarate anion.Aim: to systematize the data from fundamental and clinical studies on iron fumarate pharmacology for ID treatment using topological and metric methods of intellectual analysis.Results. The results of systematization of studies on iron fumarate pharmacology (more than 500 articles) are presented along and performed categorization of all available publications. The results of the most essential research fields assessing iron fumarate pharmacology are described in detail: (1) comparative pharmacology of iron fumarate and other iron forms; (2) an effect of various iron salts on tissue hemosiderosis; (3) synergism between iron fumarate and folates and other micronutrients; (4) an effect of microbiome state and iron fumarate absorption improved by prebiotics; (5) clinical practice of using iron fumarate for IDA treatment of women in all age groups.Conclusion. Fumarate-containing preparations are indicated in case where profound substrate-mediated support is required for pillar arms of aerobic and anaerobic energy metabolism ranging from mitochondria and cells to organismal level demanding to mobilize signal-regulatory adaptive reactions. Oral intake of fumarate salt preparations may exert milder and safer effect. In aerobic and hypoxic energy metabolism, which is typical for ID, fumarate salts may act as effective anti-stress and anti-hypoxic agents.